Use of flavor capsule cigarettes and their preliminary impact on smoking cessation in Mexico: an exploratory study - Rosibel Rodríguez-Bolaños; Paula Ramírez-Palacios; Katia Gallegos-Carrillo; Arlette Chávez-Iñiguez; Daimarelys Lara; Deborah J. Ossip; Ana Paula Cupertino; Francisco Cartujano-Barrera (Journal of Health, Population and Nutrition)
Abstract Background No study has assessed the impact of flavor capsule cigarettes (FCCs) on smoking cessation. Thus, the purpose of this exploratory study was to assess (1) the sociodemographic and smoking-related characteristics associated with using FCCs, and (2) the preliminary impact of FCCs on smoking cessation. Methods This study is a secondary data analysis of a single-arm study with 100 individuals living in Mexico who smoked and received a smoking cessation mHealth intervention and pharmacotherapy support. The primary outcomes were self-reported and biochemically verified 7-day smoking abstinence at Month 3. Results Just over one-third of participants (36%) used FCCs, with a preference for one capsule and menthol/mint flavor. Compared to participants who smoked non-FCCs, participants who smoked FCCs were (1) younger, (2) more likely to be women, and (3) more likely to smoke less than 10 cigarettes per day (CPD; all p’s < 0.05). After controlling for all significant associations, age younger than 50 years old (AOR = 3.26, 95% CI 1.25–8.51) and being a woman (AOR = 3.62, 95% CI 1.41–9.35) were positively and independently associated with smoking FCCs. Treating those lost to follow-up as participants who continued smoking, 41.7% (15/36) of participants who smoked FCCs self-reported smoking abstinence at month 3 compared to 42.2% (27/64) of participants who smoked non-FCCs (p = 0.96). Furthermore, 33.3% (12/36) of participants who smoked FCCs were biochemically verified abstinent at Month 3 compared to 18.8% (12/64) of participants who smoked non-FCCs (p = 0.10). Conclusions Younger age and being a woman were associated with using FCCs. Self-reported smoking abstinence at Month 3 was comparable between participants who smoke FCCs and non-FCCs. However, biochemically verified abstinent at Month 3 was higher among participants who smoke FCCs compared to participants who smoke non-FCCs, although the difference was not statistically significant. Prospective and adequately powered comparisons must be made between individuals who smoke FCCs and non-FCCs to effectively assess differences in smoking abstinence, and the reasons for these differences.